2016
DOI: 10.14417/ap.1070
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Interpersonal Self-Efficacy Scale: Estudo de adaptação e validação da versão Portuguesa

Abstract: A Teacher Interpersonal Self-Efficacy Scale ) é uma escala de avaliação da autoeficácia para professores, sendo constituída por 24 itens que se organizam em torno de uma estrutura de 3 fatores: (1) IntroduçãoA autoeficácia pode ser definida como a crença que um indivíduo tem acerca das suas próprias capacidades para organizar e executar cursos de ação necessários para realizar uma tarefa específica. O indubitável valor preditivo da autoeficácia dos professores no seu desempenho profissional, no processo de en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…In our study, the correlation coefficients among the subfactors were calculated between 0.49 and 0.65. These values are in parallel with the results of Çapri and Kan's [33] and Garcia-Ros, Fuentes and Fernandez's [47] and Moura and Costa's [48] studies that arrived at correlation values between 0.45-0.54 and 0.50-0.56 and 0.49-0.54 respectively. In Brouwers and Tomic's [5] study, the correlations coefficients were calculated between 0.32 and 0.57.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, the correlation coefficients among the subfactors were calculated between 0.49 and 0.65. These values are in parallel with the results of Çapri and Kan's [33] and Garcia-Ros, Fuentes and Fernandez's [47] and Moura and Costa's [48] studies that arrived at correlation values between 0.45-0.54 and 0.50-0.56 and 0.49-0.54 respectively. In Brouwers and Tomic's [5] study, the correlations coefficients were calculated between 0.32 and 0.57.…”
Section: Discussionsupporting
confidence: 87%
“…Factor loadings of the items that belonged to the subfactors, ranged between 0.55 and 0.82. Same values differed between 0.59 and 0.81 in Çapri and Kan's (2006) [33] study, and between 0.36 and 0.96 in Garcia-Ros, Fuentes and Fernandez's [47] study and between 0.52 and 0.90 in Moura and Costa's [48] study and between 0.45 and 0.90 in Brouwers and Tomic's [5] study. The results of the correlation analysis showed that the subscales were moderately related to each other, and all were highly correlated with the total TISES score.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, Cherniss (1993) has proposed the assessment of professional self-efficacy in three domains: tasks, organization, and relationships. This proposal has paved the way to assess teachers' interpersonal self-efficacy as their perceptions about the ability to develop and sustain positive relationships with students, school administration, and peers (Moura and Costa 2016). These perceptions of teachers' interpersonal self-efficacy are affected by general self-efficacy antecedents (e.g.…”
Section: 1interpersonal Resourcesmentioning
confidence: 99%
“…In this study, teacher interpersonal resources are conceptualized according to two indicators: interpersonal self-efficacy and student-teacher relationships. Interpersonal self-efficacy involves the teacher's beliefs about the ability to develop and sustain positive relationships with school administration, peers, and students (Moura and Costa 2016). Teacher-student relationships refer to the quality of pedagogical interaction when managing aspects such as closeness and conflict (Pianta 2001).…”
Section: Introductionmentioning
confidence: 99%